Development of a model for recognizing various objects and tools in a collaborative robot workspace - Yevsieiev, V.; Amer Abu-Jassar; Maksymova, S.; Demska, N. (My University, 2025)
The article discusses the development of a model for recognizing objects and tools in the robot's workspace, which is based on computer vision and machine learning methods to ensure safe interaction within the framework of Industry 5.0. The model allows increasing the accuracy and reliability of object recognition in complex conditions, adapting robots to changing tasks. The results can be used for integration into robotic platforms operating in flexible manufacturing environments, ensuring flexible automation and a human-centric approach.
Keywords: Object Recognition; Robotic Systems